Women's perspectives on long-acting reversible contraception: a critical scoping review of qualitative research. Issue 6 (3rd July 2021) - Morison, Tracy; Eagar, Daygan
ABSTRACT: Long-acting Reversible Contraception (LARC) has significant promise both from a public health outlook and a social justice perspective. However, if women's empowerment is to be supported, then perspectives and experiences of LARC must be considered. This scoping review assesses research about contraceptive users' perspectives and experiences of contraceptive decision-making and practices. A content analysis was conducted to identify research trends in qualitative studies of contraceptive-user perspectives (n = 54), located by means of a systematic search. Interpreting findings through a reproductive justice lens, three main limitations in the scholarship were identified, viz., (1) an instrumentalist, individual-level focus; (2) a lack of consideration for diverse perspectives; and (3) an uncritical focus on young women. While the small body of qualitative research on LARC offers some valuable insights, when viewed from a sexual and reproductive justice perspective, it is not sufficiently user-centered or grounded within the reproductive politics surrounding contraceptive care and provision. Research is needed that draws on appropriate social theory; widens its focus beyond dominant groups; and is cognizant of the multi-level power relations surrounding LARC. Such work provides a nuanced picture of the complex social and contextual factors at play and inform person-centered approaches in sexual and reproductive health policy and programming.